2021
DOI: 10.1111/eje.12653
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of enhanced video‐based learning on removable partial denture module

Abstract: Introduction:The application of video-based learning in dentistry has been widely investigated; however, the nature of on-screen video enhancements of the video has been minimally explored in the literature. This study investigated the effectiveness of an in-class and on-demand enhanced video to support learning on removable partial dentures in terms of knowledge acquisition, perception and clinical skill performance.Methods: Fifty-four dental students enrolled in 2018 were recruited as participants and assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Similar to the current study, Abd‐Shukor et al 19 . reported that videos enhanced with subtitles of the presenter's dialog, text bullet points and summary text pages improved the students’ knowledge retention.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similar to the current study, Abd‐Shukor et al 19 . reported that videos enhanced with subtitles of the presenter's dialog, text bullet points and summary text pages improved the students’ knowledge retention.…”
Section: Discussionsupporting
confidence: 86%
“…A similar finding was already reported by Schlafer 16 in that didactic elements such as questions in videos stimulate reflection. Furthermore, Abd‐Shukor et al 19 . reported that adding text to instructional videos enhances students’ ability to improve their theoretical knowledge by recalling and transferring that information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantage of video-based learning has been demonstrated in previous studies. [23][24][25][26][27] During the whole training process, the video clip demonstrating the use of the dental operating microscope and the instrument removal procedure was uploaded online and was available for trainees to enhance the learning process.…”
Section: The Questionnairesmentioning
confidence: 99%